STORE LOYALTY ON ONLINE STORE CUSTOMERS IN INDONESIA - Rossyta Dewi; Dudi Anandya (Journal of Management and Business, 2015)
Nowadays, online retailing in Indonesia had flourished and estimated to be one of the most prominent foundation to boost Indonesia’s economic growth. Aiming to anticipate the trend, this research is written in order to gain a deeper understanding about the loyalty behavior among online store customers in Indonesia by investigating the influence of store image and perceived value towards online store loyalty. Data in this research were collected from online questioner sent troughout online forum and social media. Structural Equation Modelling method is used here along with software Lisrel 8.80. Past studies found that online store image, perceived utilitarian value and perceived hedonic value positively influences one of several dimensions of loyalty, repurchase intention. This research proves that online store image directly influences perceived utilitarian value, perceived hedonic value and online store loyalty while neither perceived utilitarian value nor perceived hedonic value directly influences online store loyalty. This research also found that ease of use and trustworthiness as the most reliable and influential dimensions in online store image.